Peran Sistem Informasi Akuntansi dalam Meningkatkan Kualitas Laporan Keuangan Perusahaan: Kajian Literatur - Putri Wulandari Nasution; Tria Wulandari; David Efendi (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study aims to examine the extent to which the implementation of an Accounting Information System (AIS) affects the quality of a company's financial reports. By providing relevant, fast, and accurate information, an AIS can simplify the process of recording transactions, preparing reports, and supporting management decision-making. Furthermore, an AIS plays a role in strengthening the planning, control, and financial management functions to be more effective. The method used is a literature review with sources from scientific articles, accounting journals, and academic publications obtained through Google Scholar. The results of the study indicate that the implementation of an AIS contributes to increasing the relevance, reliability, comparability, and timeliness of financial reports. Furthermore, the development of an AIS through automation, database integration, strengthening internal controls, and utilizing digital technology can promote transparency, accountability, and company effectiveness. Thus, optimizing an AIS has the potential to improve the quality of financial reports while strengthening company competitiveness